Analysis of Plasma MicroRNAs as Predictors and Biomarkers of Aging and Frailty in Humans. (18th July 2018) - Rusanova, Iryna; Diaz-Casado, María E.; Fernández-Ortiz, Marisol; Aranda-Martínez, Paula; Guerra-Librero, Ana; García-García, Francisco J.; Escames, Germaine; Mañas, Leocadio; Acuña-Castroviejo, Darío
Abstract : Although circulating microRNAs (miRNAs) can modulate gene expression and affect immune system response, little is known about their participation in age-associated frailty syndrome and sarcopenia. The aim of this study was to determine miRNAs as possible biomarkers of age and frailty and their correlation with oxidative and inflammatory state in human blood. Three inflammation-related miRNAs (miR-21, miR-146a, and miR-223) and one miRNA related with the control of melatonin synthesis (miR-483) were analyzed. Twenty-two healthy adults, 34 aged robust, and 40 aged fragile patients were selected for this study. The expression of plasma miRNAs was assessed by RT-qPCR; plasma cytokines (IL-6, IL-8, IL-10, and TNF α ) were analyzed by commercial kits, and plasma advanced oxidation protein products (AOPP) and lipid oxidation (LPO) were spectrophotometrically measured. Fragile subjects had higher miR-21 levels than control subjects, whereas miR-223 and miR-483 levels increased at a similar extend in both aged groups. All cytokines measured increased in aged groups compared with controls, without differences between robust and fragile subjects. The fragile group had a TNF α /IL-10 ratio significantly higher than robust and control groups. Aged groups also had higher AOPP and LPO levels than controls. Women presented higher AOPP and LPO levels and increased expression of miR-483 compared with men. Positive correlations between miR-21 and AOPP and between miR-483 and IL-8 were detected. The expression of miR-21 and the TNF α /IL-10 ratio were correlated positively with the presence of frailty, which suggests that these markers can be considered as possible biomarkers for age-related frailty.